How negative out-party affect influenced public attitudes about the coronavirus crisis in Norway - Ryan, Alexander (Frontiers in Political Science, 2022)
Research on affective polarization and negative partisanship toward disliked out-parties has increased significantly in recent years. However, there are surprisingly few studies that actually examine its political consequences, especially outside of the US. This study relies on two survey experiments to examine how dislike toward out-parties affected how Norwegian citizens evaluated the country's response to the coronavirus crisis. The first experiment follows the example of previous research on the US case and tests how out-party dislike measured before the coronavirus outbreak affected subsequent attitudes about how Norway and the conservative government had managed the crisis. The second experiment then randomly assigns party cues to a policy proposal included in the country's economic rescue package and tests whether like-dislike party evaluations moderate the effect of receiving the party cues. Overall, the results show that out-party dislike predicted attitudes to the government's response, but, contrary to studies focusing on the US case, this effect was either nonexistent or weaker for those who rated the country's response. Additionally, while out-party cues polarized opinions to the proposal, the moderating effect of out-party dislike was only more consistently found for those who received party cues from the populist-right party.